Weekday effect of surgery on in-hospital outcome in pancreatic surgery: a population-based study - Uttinger, Konstantin L.; Niezold, Annika; Weimann, Lina; Plum, Patrick Sven; Baum, Philip; Diers, Johannes; Brunotte, Maximilian; Rademacher, Sebastian; Germer, Christoph-Thomas; Seehofer, Daniel; Wiegering, Armin (Langenbeck's archives of surgery, 2025)
Importance: There is conflicting evidence regarding weekday dependent outcome in complex abdominal surgery, including pancreatic resections. Objective: To clarify weekday-dependency of outcome after pancreatic resections in a comprehensive nationwide context. Design: Retrospective cross-sectional study of anonymized nationwide hospital billing data (DRG data). Setting: Germany between 2010 and 2020.Participants and exposure: all patient records with a procedural code for a pancreatic resection. Main outcome and measures: Primary endpoint was complication occurrence and failure to rescue, i.e. mortality in case of complications, by weekday of index surgery. Results: 94,661 patient records with a pancreatic resection were analyzed, of whom 45.2% were female. Mean age was 65.3 years. In 46.3% of all patient records, the main diagnosis was pancreatic carcinoma. The most common index surgery was pancreaticoduodenectomy (61.2%). Occurrence of at least one of predefined complications was 67.6% (64,029 cases) and was highest following a Monday index surgery. In-hospital mortality in case of at least one complication, i.e. failure to rescue (FtR), accounted for 8,040 deaths (97.7% of 8,228 total deaths, 12.6% FtR, 8.7% in-hospital mortality). FtR was highest (13.1%) following a Monday index surgery and lowest (11.8%) after a Thursday index surgery. Overall in-hospital mortality followed the same trend as FtR. In a multivariable logistic regression, in the overall cohort, in addition to increased age, frailty, male sex, benign entities, and total pancreatectomy performance, Wednesday (adjusted Odd’s Ratio, OR, 0.92, 95% Confidence Interval, CI, 0.85–0.99) and Thursday (adjusted OR, 0.89, CI, 0.82–0.96) index surgeries were associated with lower FtR in reference to Monday. Stratified by patient volume, complication occurrence and FtR was only dependent of the weekday of index surgery in low volume hospitals. Conclusions and relevance: Pancreatic resections are complex procedures with high complication rates and FtR, resulting in high in-hospital mortality. Complication occurrence and FtR is dependent on the weekday of index surgery and mediates the same distribution pattern for overall in-hospital mortality. Stratified by patient volume, this weekday dependency of the index surgery on complication occurrence and FtR was only observed in low volume hospitals.